Perlindungan Hukum Terhadap Anak Dibawah Umur Pasca Perceraian Perspektif Undang-Undang Perlindungan Anak No 35 Tahun 2014 - Harahap, Hilal Haitami; Harahap, Mhd. Yadi (Jurnal EL-QANUNIY: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2024)
This scholarly inquiry aims to ascertain the legal status of offspring conceived within matrimonial bonds, as well as the statutory regulations concerning Custody rights post-Divorce. Through the application of normative jurisprudential analysis, the findings indicate that the status of children conceived within such unions holds legal validity and constitutes a significant aspect of the child's welfare. This is stipulated under the provisions of Law Number 1 of 1974, specifically in Chapter IX, Articles 42 to 43. Concerning Child Protection and Custody rights post-Divorce, the law mandates that both parents continue their responsibilities to nurture and educate their offspring, prioritizing the child's best interests. Should conflicts arise over Custody, the judiciary is tasked with resolving these by issuing rulings, as stipulated in Article 41(a) of Law No. 1 of 1974 on Marriage. The legal onus for covering the child's upkeep and educational expenses rests with the father. However, should the father prove incapable of meeting these responsibilities, judicial discretion under Article 41(b) allows for the assignment of these financial obligations to the mother. Additionally, the court holds the authority to mandate financial support from the former husband and may specify the financial duties of the former wife. The research results show that the main aim of Child Protection is to ensure that all children's rights are fulfilled so that they are able to live and develop well, and contribute in accordance with human values and dignity. This includes getting protection against acts of violence and discrimination to achieve the vision of creating a quality, virtuous and prosperous Indonesian generation.